Bidirectional pressure: a mini review of ventilator-lung-kidney interactions - Kumar, Avnee; Epler, Katie; DeWolf, Sean; Barnes, Laura; Hepokoski, Mark (Frontiers in Physiology, 2024)
Acute kidney injury and respiratory failure that requires mechanical ventilation are both common complications of critical illnesses. Failure of either of these organ systems also increases the risk of failure to the other. As a result, there is a high incidence of patients with concomitant acute kidney injury and the need for mechanical ventilation, which has a devasting impact on intensive care unit outcomes, including mortality. Despite decades of research into the mechanisms of ventilator-lung-kidney interactions, several gaps in knowledge remain and current treatment strategies are primarily supportive. In this review, we outline our current understanding of the mechanisms of acute kidney injury due to mechanical ventilation including a discussion of; 1) The impact of mechanical ventilation on renal perfusion, 2) activation of neurohormonal pathways by positive pressure ventilation, and 3) the role of inflammatory mediators released during ventilator induced lung injury. We also provide a review of the mechanisms by which acute kidney injury increases the risk of respiratory failure. Next, we outline a summary of the current therapeutic approach to preventing lung and kidney injury in the critically ill, including fluid and vasopressor management, ventilator strategies, and treatment of acute kidney injury.Finally, we conclude with a discussion outlining opportunities for novel investigations that may provide a rationale for new treatment approaches.